Bridging Automation and Innovation: Evaluating e- FOAS and AI Synergies for Better Governance Outcomes (Journal of Politics and International Studies, 2025)
This assessment reviews the current progress of the e-Filing and Office Automation System (e-FOAS) in Punjab, a significant ICT project initiated by the provincial government to enhance administrative efficiency, ensure transparency, and improve public service delivery, however, its implementation varies across different regions and continues to encounter various systemic and structural challenges. The initiative has nonetheless produced tangible results, supported by key provincial policies outlined in the Punjab Rules of Business, 2011. To date, over four million files have been handled through the system, and communication among departments has become more streamlined (Latif, 2025). However, several challenges persist. Adoption across departments is inconsistent, with only 30 out of 50 administrative units reaching Level 3 implementation. Training coverage remains incomplete, with just 34 of the planned 70 sessions conducted so far. Many offices still depend on a hybrid of manual and digital processes, data security standards are insufficient, and there is notable resistance from mid-level officials. Public confidence in the system’s security is also relatively low, with only 38.3% of users expressing trust in data protection measures. This analysis indicates that incorporating Artificial Intelligence (AI) for functions like predictive routing, workflow analysis, and automatic document categorization could significantly enhance service delivery.